Index lesion characterization by 11C‐Choline PET/CT and Apparent Diffusion Coefficient parameters at 3 Tesla MRI in primary prostate carcinoma. Issue 1 (22nd September 2015) - Hernández‐Argüello, Miguel; Quiceno, Hernán; Pascual, Ignacio; Solorzano, José L.; Benito, Alberto; Collantes, María; Rodríguez‐Fraile, Macarena; Pardo, Javier; Richter, José A.
Abstract : BACKGROUND: Index lesion characterization is important in the evaluation of primary prostate carcinoma (PPC). The aim of this study was to analyze the contribution of 11 C‐Choline PET/CT and the Apparent Diffusion Coefficient maps (ADC) in detecting the Index Lesion and clinically significant tumors in PPC. METHODS: Twenty‐one untreated patients with biopsy‐proven PPC and candidates for radical prostatectomy (RP) were prospectively evaluated by means of Ultra‐High Definition PET/CT and 3T MRI, which included T2‐weighted imaging (T2WI) and ADC maps obtained from diffusion weighted imaging (DWI). Independent experts analyzed all the images separately and were unaware of the pathological data. In each case, the Index lesion was defined as the largest tumor measured on histopathology (Index H). In addition, the largest lesion observed on MRI (Index MRI) and the highest avid 11 C‐Choline uptake lesion (Index PET) were obtained. The Gleason scores (GS) of the tumors were determined. PET/CT and ADC map quantitative parameters were also calculated. Measures of correlation among imaging parameters as well as the sensitivity (S), specificity (Sp), negative and positive predictive values (NPV and PPV) for tumor detection were analyzed. All data was validated with the pathological study. RESULTS: In the morphological study, 139 foci of carcinoma were identified, 47 of which corresponded to clinically significant tumors (>0.5 cm 3 ). The remaining foci presented a maximum diameter ( d max ) of 0.1 cm ± SD 0.75 and were not classified as clinically significant. Thirty‐two tumors presented a GS (3 + 3), nine GS (3 + 4), and six GS (4 + 3). A total of 21 Index H ( d max = 1.37 cm SD ± 0.61) were identified. The S, Sp, NPV, and PPV for tumor detection with PET were 100%, 70%, 83%, 100%, and for MRI were 46%, 100%, 100%, 54%, respectively. Both Index PET and Index MRI were complementary and identified 95% of the Index H when quantitative criteria were used. CONCLUSION: In spite of the fact that PET imaging has higher tumor sensitivity than MRI, 11 C‐Choline PET and ADC maps have complementary roles in the evaluation of Index Lesion in PPC. Index PET and Index MRI could be complementary targets in the therapeutic planning of PPC. Prostate 76:3–12, 2016 . © 2015 Wiley Periodicals, Inc.